Perubahan Bahasa Indonesia Dalam Komunikasi Modern dan Implikasinya Bagi Generasi Muda - Pangaribuan, Devy J.R; Pulungan, Hendra Kurnia; Manurung, Elisabet Magdalena; Harefa, Rili Angelica; Hutasoit, Sartika Br; Nasution, Abidah Ramadhani; Marsyah, Aralia Putri; Dewi, Artika Sardiana; Sari, Defi Mawar; Sinaga, Husna Khoiri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses changes in Indonesian language in modern communication and its implications for the younger generation. The research method used is descriptive qualitative with data collection techniques through observation on social media (WhatsApp, Instagram, and Twitter) and interviews with 10 respondents aged 15-25 years. The results of the study indicate significant changes in four main aspects of language: phonology, morphology, lexical, and syntax. These changes are characterized by the use of foreign terms, abbreviations, and simplification of sentence structures that are dominant among the younger generation. The data shows that 60% of posts on social media use abbreviated phonological spelling, while 80% of respondents admitted to using abbreviations in daily conversations. The implications of this language change include positive impacts in the form of increased linguistic creativity and ease of cross-cultural communication, as well as negative impacts in the form of decreased ability to speak standard Indonesian and the potential for the erosion of national language identity. The conclusion of this study confirms that language change in modern communication is natural but has the potential to reduce formal language skills if not balanced with good language education and literacy. Efforts to preserve the Indonesian language require serious attention through formal education and campaigns on social media to maintain the existence of the national language amidst the flow of globalization.